The Role of Women Ulama in the Development of Islamic Education - Norlaila; Nuryadin; Yaqin, Husnul (LETIGES, 2025)
This study aims to analyze the role of women ulama in South Kalimantan in advancing Islamic education through pesantren leadership, inclusive educational approaches, and adaptation of digital technology in da'wah. This research employed a qualitative descriptive approach with a case study type to explore the real-life context of women's leadership in Islamic education. The primary data was obtained from 25 female ulama. Data collection techniques included semi-structured interviews, participatory observation, and document analysis of da'wah content disseminated through social media. To ensure the validity of the data, triangulation was applied by comparing the findings from different data sources and techniques. The data were analyzed using thematic analysis, involving data reduction, categorization, and theme identification to reveal patterns related to the roles and contributions of women ulama. The results showed that female ulama in this region can manage pesantren with an inclusive and collaborative leadership style, thus creating an empathetic and friendly educational environment for both female and male Santri. In addition, the inclusive approach to education allows female ulama to accommodate the specific needs of female congregants through discussions on relevant issues, such as family education, health, and women's rights in Islam. Other findings show that female ulama has successfully utilized digital technologies, such as YouTube, Instagram, Facebook, and TikTok Live, to spread da'wah to a broader and cross-generational audience, especially those familiar with the technology. This adaptation allows them to deliver religious messages that are relevant and accessible, thus strengthening women's participation in religious discussions in the digital era. Overall, this study shows that women ulama in South Kalimantan play an important role in Islamic education responsive to the congregation's needs, whether through leadership in pesantren, gender-sensitive education, or digital adaptation in da'wah. The results of this study provide a new perspective on the importance of the role of women ulama in strengthening Islamic education that is inclusive and adaptive to the times.